Fernando Blanco White, «A Spanish Prisoner in the Ruins of Napoleon’s Empire. The diary of Fernando Blanco White’s Flight to Freedom». Ed. e intr. de Christopher Schmidt-Nowara (†); prefacio de Beatrice Forbes Manz y Matthew Ehrlich - Durán López, Fernando (Cuadernos de Ilustración y Romanticismo, 2018)
Reseña bibliográfica